(In)effective tax policy vs. fiscal (un)sustainability: evidence from Polish municipal government level. (22nd December 2021) - Klonowska, Alina; Uryszek, Tomasz
The main goal of the paper is to investigate the impact of tax preferences on the fiscal sustainability of Polish communes. Such a goal is accompanied by the following research hypothesis: resignation from tax preferences would enable obtaining a primary budget surplus in the municipal government sector in Poland. The research period covers yearly observations and estimations made between 2003 and 2018. Empirical evidence confirms the research hypothesis to be true. We found out that Polish communes should strive to stabilise the level of public debt and avoid excessive indebtedness. What is important, the communes would not have to abandon the use of all fiscal instruments (including reliefs and exemptions) to reach this goal. It would be enough to be more responsible about using fiscal tools and to make more effort to collect tax liabilities.